Prokaryotic taxonomy and functional diversity assessment of different sequencing platform in a hyper-arid Gobi soil in Xinjiang Turpan Basin, China - Zhang, Zhidong; Zhu, Jing; Ghenijan, Osman; Chen, Jianwei; Wang, Yuxian; Jiang, Ling (Frontiers in Microbiology, 2023)
Turpan Basin located in the eastern Xinjiang is a typical arid inland basin with extremely scarce water resources and a fragile ecosystem. Prokaryotic communities with unique genetic and physiological modifications can survive and function in such harsh environments, offering diverse microbial resources. However, numerous microbes can enter the viable but non-culturable state because of drought stress in the desert soil. In this work, next generation sequencing (NGS) technology based on DNA nanoball sequencing platform (DNBSEQ-G400) and sequencing-by-synthesis platform (NovaSeq 6000) were applied to analyze the prokaryotic diversity in three hyper-arid Gobi soils from Flaming Mountain, Toksun, and Kumtag. The comparison between two platforms indicated that DNBSEQ-G400 had better repeatability and could better reflect the prokaryotic community of this hyper-arid region. The diversity analysis based on DNBSEQ-G400 identified a total of 36 bacterial phyla, including Pseudomonadota, Bacteroidota, Bacillota, Actinomycetota, Methanobacteriota, Acidobacteriota, Nitrososphaerota, and Planctomycetota. The environmental factors, including soluble salt, available potassium, total nitrogen, and organic matter, were positively correlated with the abundance of most prokaryote. In addition, the prokaryotic community assembly in hyper-arid soil was well described by neutral-based models, indicating that the community assembly was mainly controlled by stochastic processes. Finally, the phylogenetic analysis of Actinomycetota proved that such extremophiles played an important role in the ecosystems they colonize. Overall, our result provides a reference for choosing the appropriate sequencing platform and a perspective for the utilization of soil microbial resources from hyper-arid regions.